Achievement motivation and its relationship with job satisfaction (A Field study on teachers of art education in Tartous city) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aims to detect the level of achievement motivation and job satisfaction among teachers of art education, and research also aims to find out the relationship between achievement motivation and job satisfaction they have, as well as knowing the impact of the interaction between (gender, qualification and experience) at the level of job satisfaction and achievement motivation among teachers of art education, the sample consisted of (125) teachers of teachers of art education in Tartous city, the tools included two measurements of achievement motivation and job satisfaction, during the academic year of (2015 - 2016) after the Validity and the Reliability was established. The descriptive approach was used. Findings showed that achievement motivation and job satisfaction level among teachers of art education was average ,as findings revealed the presence of statistically significant relationship between achievement motivation and job satisfaction among teachers, as well as the results did not show an effect of the interaction between (gender, qualification and experience) at the level of job satisfaction and achievement motivation among teachers of art education. The research proposed several suggestions about proceeding a number of related studies